2019
DOI: 10.1097/md.0000000000017031
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in complement and coagulation pathways of human placentae subjected to in vitro fertilization and embryo transfer in the first trimester

Abstract: The mechanisms underlying the potential risks of in vitro fertilization and embryo transfer (IVF-ET) have not been fully elucidated. The aim of this study was to explore changes in the complement and coagulation pathways in placentae subjected to IVF-ET in the first trimester compared to placentae from normal pregnancies. Four placenta samples in the first trimester were obtained from patients undergoing IVF-ET owing to oviductal factors only. An additional 4 control placentae were obtained from volunteers wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…All complement components along with the plasminogen precursor, the factor XIIa inhibitor precursor, the P-selectin precursor, the alpha-1-antiproteinase precursor, prothrombin, alpha-2-antiplasmin, and the coagulation factor V involved in the cascade were downregulated in CPL-treated samples. Previous studies have indicated that overactivation of this system has associated factors in many pregnancy complications as the cascade deposits several split products on the cell membrane, ultimately creating a cytotoxic cell lysis complex, inflammation, and tissue injury including free circulating anaphylatoxins such as C3a and C5a [52]. This might suggest that CPL not only treated NEB but also reduced the associated reproductive complications.…”
Section: Discussionmentioning
confidence: 99%
“…All complement components along with the plasminogen precursor, the factor XIIa inhibitor precursor, the P-selectin precursor, the alpha-1-antiproteinase precursor, prothrombin, alpha-2-antiplasmin, and the coagulation factor V involved in the cascade were downregulated in CPL-treated samples. Previous studies have indicated that overactivation of this system has associated factors in many pregnancy complications as the cascade deposits several split products on the cell membrane, ultimately creating a cytotoxic cell lysis complex, inflammation, and tissue injury including free circulating anaphylatoxins such as C3a and C5a [52]. This might suggest that CPL not only treated NEB but also reduced the associated reproductive complications.…”
Section: Discussionmentioning
confidence: 99%
“…In pregnancies resulting from in vitro fertilization and embryo transfer, the incidence of adverse pregnancy outcomes tends to be greater. Zhao et al ( 77 ) hypothesized that this may be due to changes in complement and/or coagulation pathways. Placentas were obtained in the first trimester following in vitro fertilization and embryo transfer and processed for microarray analysis.…”
Section: Complement From Implantation Through Placental Developmentmentioning
confidence: 99%
“…A soluble form of GCD59 shed from cell membranes can be measured with a highly sensitive and specific enzymelinked immunosorbent assay (ELISA) test (2). Zhao et al (10) found that downregulation of CD59 predisposed the placenta to increased complement activation and complementmediated damage as compared to normal pregnancy.…”
mentioning
confidence: 99%